INSTITUTIONAL AND INFRASTRUCTURAL MECHANISMS FOR ENHANCING REGIONAL INVESTMENT ATTRACTIVENESS: CONCEPTUAL EVIDENCE FROM UZBEKISTAN (Eureka Journal of Business, Economics & Innovation Studies, 2026)
The investment attractiveness of a territory is determined not only by macroeconomic stability and fiscal incentives, but also by the quality of local institutions and the readiness of infrastructure that investors use in everyday operations. This article examines institutional and infrastructural mechanisms for increasing regional investment attractiveness, with conceptual evidence from Uzbekistan as a reforming, double-landlocked economy in Central Asia. The study applies a qualitative analytical methodology based on institutional economics, regional development theory, investment climate studies and secondary data from international and national sources. The paper develops a Regional Investment Attractiveness Mechanism (RIAM) that links legal certainty, investment promotion, single-window services, special economic zone governance, public-private partnership instruments, transport connectivity, energy reliability, serviced industrial land, digital infrastructure and human capital. The analysis shows that institutional mechanisms reduce transaction costs and uncertainty, while infrastructural mechanisms reduce operational costs and market-access barriers. Their interaction is decisive: infrastructure becomes attractive to investors only when accompanied by predictable rules, coordinated agencies, transparent project pipelines and effective aftercare. The article contributes to the literature by integrating institutional and infrastructural determinants into a single regional investment framework and by proposing practical policy recommendations for improving regional investment governance, project readiness and sustainable infrastructure financing.
Keywords: Regional investment attractiveness; institutional mechanisms; infrastructure development; foreign direct investment; special economic zones; investment promotion; Uzbekistan.